News and sectoral comovement - Michael J. Lamla; Sarah M. Lein; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2007)
This paper tests the existence of strategic information complementarities as a source of sectoral comovement. A theoretical model derived in Veldkamp and Wolfers (2007) explains sectoral comovement by the assumption that firms rely too much on aggregate information to make output decisions. We find empirical support for this hypothesis: news on aggregate developments, on average, affect firm's production plans significantly more than news on sector-specific developments. This result is based on a rich dataset on firm survey and media releases for Germany comprising 01/1999-07/2006.
Keywords: E32; D82; 330; Media reporting; news; expectation driven business cycles; information complementarities; sectoral comovement; Branchenkonjunktur; Informationsverbreitung; Produktivität; Produktionsplanung; Deutschland